Preparation, Characterization And Properties Of Degradable Linear Low Density Polyethylene soya Powder Blends - Sung Ting, Sam (2011)
The linear low density polyethylene (LLDPE) was blended with soya powder by using Haake internal mixer at a temperature of 150°C and rotor speed of 50 rpm. The tensile properties were tested using an Instron tensometer. The thermal behaviors of the blends were analyzed using differential scanning calorimetry (DSC). The thermal stability of the blends was determined using a thermogravimetric analyzer (TGA). The soya powder content was varied from 5 to 40 wt%. Two types of compatibilisers were used to improve the interfacial adhesion of LLDPE/soya powder blends which are polyethylene grafted maleic anhydride (PE-g-MA) and epoxidised natural rubber with 50 mol%. epoxidation (ENR 50). Tensile strength and elongation at break (Eb) decreased with increasing soya powder content. The addition of PE-g-MA as a compatibiliser increased the tensile strength, Eb, and modulus of the blends. Furthermore, the addition of PE-g-MA slightly enhanced the thermal stability of the blends. On the other hand, the tensile strength, Eb and thermal stability were significantly improved by the addition of ENR 50. During natural weathering and natural soil burial for 1 year, it was observed that the incorporation of soya powder had increased the degradability after exposure. However, PE-g-MA compatibilised blends showed lower degradability than uncompatibilised blends based on tensile properties, carbonyl indices, crystallinity, weight loss and molecular weight change observations. Nevertheless, it is found that degradability of ENR 50 compatibilised blends was higher than uncompatibilised blends upon exposure